Alteraciones del metabolismo del fierro post bypass gástrico - Marambio G., Andrés; Castro P., Fabiola; Marambio G., Juan Pablo (Revista Hospital Clínico Universidad de Chile, 2010)
A complication of bariatric surgery and especially gastric bypass are nutritional deficiencies that occur in the long term, being very important iron deficiency and anemia. Several mechanisms influence this, highlighting the exclusion of the duodenum and part of jejunum. Is in these places which have been described the presence of the iron transporter, which is over expressed in situations of iron deficiency. Special adaptation mechanisms may explain the maintenance of iron homeostasis in these patients. Associated with this, they require a specific nutritional management including diet and special supplements, however, despite this there is a proportion of patients who will develop the deficit and in some cases even become a major problem. Today we know several pathways, proteins and transporters involved in iron metabolism, mainly at the level of absorption, but little is known about the changes that occur at this level in people undergoing deficit, such as patients undergoing gastric bypass and the changes that occur here to optimize it metabolism. Here you will see a review of the iron metabolism and then a description of the changes that occur in its physiology following a gastric bypass.